Controlling Band Alignment at the Back Interface of Cadmium Telluride Solar Cells using ZnTe and Te Buffer Layers. (15th January 2019) - Alfadhili, Fadhil K.; Phillips, Adam B.; Liyanage, Geethika K.; Gibbs, Jacob M.; Jamarkattel, Manoj K.; Heben, Michael J.
ABSTRACT: Formation of a low barrier back contact plays a critical role in improving the photoconversion efficiency of the CdTe solar cells. Incorporating a buffer layer to minimize the band bending at the back of the CdTe device can significantly lower the barrier for the hole current, improving open circuit voltage (VOC ) and the fill factor. Over the past years, researchers have incorporated the both ZnTe and Te as buffer layers to improve CdTe device performance. Here we compare device performance using these two materials as buffer layers at the back of CdTe devices. We show that using Te in contact to CdTe results in higher performance than using ZnTe in contact to the CdTe. Low temperature current density-voltage measurements show that Te results is a lower barrier with CdTe than ZnTe, indicating that Te has better band alignment, resulting in less downward bending in the CdTe at the back interface, than ZnTe does.